Monochromophoric Design Strategy for Tetrazine-Based Colorful Bioorthogonal Probes with a Single Fluorescent Core Skeleton - Lee, Youngjun; Cho, Wansang; Sung, June; Kim, Eunha; Park, Seung Bum (Journal of the American Chemical Society, 2018)
Fluorogenic bioorthogonal probes are ideal for fluorescent imaging in live cell conditions. By taking advantage of the dual functionality of tetrazine (Tz), as a bioorthogonal reaction unit as well as a fluorescence quencher, a fluorophore-Tz conjugate (FLTz) has been utilized for fluorescent live cell imaging via inverse electron-demand Diels-Alder (iEDDA) type bioorthogonal reactions. However, most FLTz strategies rely on a donor-acceptor-type energy transfer mechanism, which limits red-shifting of probes' emission wavelength without deterioration of the fluorescent turn-on/off ratio. To address this constraint, herein we present a monochromophoric design strategy for making a series of FLTzs spanning a broad range of emission colors. For the systematic comparison of design strategies with minimized structural differences, we selected indolizine-based emission-tunable Seoul-Fluor (SF) as a model fluorophore system. As a result, by inducing strong electronic coupling between Tz and π-conjugation systems of an indolizine core, we efficiently quench the fluorescence of SF-tetrazine conjugates (SFTzs) and achieved more than 1000-fold enhancement in fluorescence after iEDDA reaction with trans-cyclooctene (TCO). Importantly, we were able to develop a series of colorful SFTzs with a similar turn-on/off ratio regardless of their emission wavelength. The applicability as bioorthogonal probes was demonstrated with fluorescence bioimaging of innate microtubule and mitochondria using docetaxel-TCO and triphenylphosphonium-TCO in live cells without washing steps. We believe this study could provide new insight for the reliable and generally applicable molecular design strategy to develop bioorthogonal fluorogenic probes having an excellent turn-on ratio, regardless of their emission wavelength.
Keywords: Bioorthogonal reactions; Electronic coupling; Emission wavelength; Energy transfer mechanisms; Fluorescence quenchers; Fluorescent imaging; Fluorogenic probes; Structural differences; Cell Line, Tumor; Cycloaddition Reaction; Fluorescent Dyes; HeLa Cells; Heterocyclic Compounds; Humans; Mitochondria; Models, Molecular; Optical Imaging